Suárez’s solution to the problem of evolution or dogmatic progress - García Martínez, Fidel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 1948)
The problem of the evolution or progress of the dogma is posed in its fundamental or substantive terms, to reach the solution that admits or will have to be given according to the doctrine of Suárez. This problem arises from the contrast between a dogmatic principle and a historical fact, which raises the following question: has the revelation been expanded? Or has there been a new increase in the deposit of faith by the addition of foreign elements or elements not already contained in it? And, if not, how then is the historical fact explained? The author is inclined to believe that Suárez’s opinion is more in accordance with the feelings of the ancient theologians and the laws of human thought and language.